2012
DOI: 10.1097/nne.0b013e31826f2c04
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Reasoning and Online Social Media

Abstract: Undergraduate nursing students are frequent users of social media sites; however, the ethical or professional implications surrounding the use of online social networking sites are ambiguous and understudied. Faculty guidance is needed if students are to gain the necessary skills and values to appropriately use social media while maintaining professional accountability. The authors discuss the outcomes of a study that assessed their students' sensitivity to posting clinical information on social media sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…A longitudinal study conducted on the basis of and inspired by Kohlberg's theory showed that moral development is strongly linked to age, education and IQ. However, the experience of school tends to favour a predominance of stages 1 and 4 (reward/punishment and law and order) [19]. The sharing of ethical and moral values in an educational context is seen as equivalent to teaching ethics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A longitudinal study conducted on the basis of and inspired by Kohlberg's theory showed that moral development is strongly linked to age, education and IQ. However, the experience of school tends to favour a predominance of stages 1 and 4 (reward/punishment and law and order) [19]. The sharing of ethical and moral values in an educational context is seen as equivalent to teaching ethics.…”
Section: Discussionmentioning
confidence: 99%
“…Trainers should include policies on the use of social media in their curricula and teach students to use them appropriately from the very start of their courses, promoting discussion and analysis on the subjects of confidentiality, privacy and professionalism [38]. Similarly, there is a focus on ethical awareness and hence on building moral development [19,20]. According to Kohlberg, there are six stages of moral development: [1] reward/punishment [2] individualism and instrumental purpose [3] good boy/girl [4] law and order [5] social contract [6] conscience and universal principles [39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations